The effect of auditory experience on speech perception, localization, and functional performance of children who use a cochlear implant and a hearing aid in opposite ears. - Ching TYC; Hill M; Brew J; Incerti P; Priolo S; Rushbrook E; Forsythe L (International Journal of Audiology, 2005)
This study was aimed at determining the effect of auditory experience on binaural benefits from using a cochlear implant and a hearing aid in opposite ears. Eighteen children were evaluated using tests of speech perception, horizontal localization, and functional performance when they used either a cochlear implant alone (CI) or a cochlear implant with a hearing aid (CIHA). Eight were experienced CIHA users, whereas ten had not worn a hearing aid in the non-implanted ear for up to eight years prior to participation. All children were fitted with a hearing aid in the non-implanted ear using the NAL-RP prescription, and the hearing aids were fine-tuned individually using a paired-comparisons procedure and a loudness balancing test. Evaluation results indicated that performance for all measures was significantly better with CIHA than with CI for both groups of children. We conclude that children who receive a unilateral cochlear implant should be encouraged to wear a hearing aid in the opposite ear where there is usable residual hearing.